Anticancer activities of natural abietic acid - Ahmad, Bashir; Tian, Chuan; Tang, Ji-Xin; Dumbuya, John Sieh; Li, Wen; Lu, Jun (Frontiers in Pharmacology, 2024)
Cancer is the main cause of death in the world. There are several therapies that are in practice for cancer cure including radiotherapy, chemotherapy, and surgery. Among the chemotherapies, natural products are considered comparable safe, easily available and cost effective. Approximately 60% of cancer approved FDA drugs are natural products including vinblastine, doxorubicin, and paclitaxel. These natural products have complex structures due to which they work against cancer through different molecular pathways, STAT3, NF-Kb, PI3K/AKT/mTOR, cell cycle arrest, mitochondrial dependent pathway, extrinsic apoptosis pathway, autophagy, mitophagy and ferroptosis. Abietic acid (AA) is a natural abietane diterpenoid compound from Pinus palustris and Pimenta racemose var. grissea with different pharmacological activities including anti-inflammatory, anti-convulsant, anti-obesity and anti-allergic. Recently it has been reported with its anticancer activities through different molecular mechanisms including NF-Kb, PI3K/AKT, call cycle arrest at G0/G1 phase, mitochondrial dependent pathway, extrinsic apoptosis pathway, AMPK pathway and ferroptosis pathways. The literature survey reveals that there is no review on AA anticancer molecular mechanisms, therefore in current review, we summarize the anticancer molecular mechanisms of AA.